Negative electrode for lithium secondary battery and method for producing same
Through the double-layer negative electrode active layer structure and magnetic field orientation control, the problems of long charging time, insufficient capacity and poor fast charging performance of lithium secondary batteries are solved, and the lithium secondary battery performance of high capacity, fast charging and excellent life is achieved.
Patent Information
- Application Number
- CN202480009318.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-11
- Filing Date
- 2024-08-05
- Publication Date
- 2025-09-05
AI Technical Summary
Due to the limitations of negative electrode active materials, existing lithium secondary batteries have long charging times, insufficient charging and discharging capacities, and poor fast charging performance and life characteristics.
A double-layer negative electrode active layer structure is adopted. The first layer contains a carbon-based negative electrode active material with a high orientation index, and the second layer contains a silicon-based negative electrode active material. The orientation is controlled by applying a magnetic field, and an appropriate amount of silicon material is combined to improve the charge and discharge capacity. The lithium ion migration path is optimized by controlling the orientation index and porosity.
It achieves high charge and discharge capacity, excellent life characteristics and fast charging performance, shortens charging time and improves the overall performance of lithium secondary batteries.
Smart Images

Figure BDA0005517167570000241 
Figure BDA0005517167570000251 
Figure BDA0005517167570000271
Abstract
Description
Technical Field
[0001] The present disclosure relates to a negative electrode for a lithium secondary battery and a method for manufacturing the same.
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2023-0105352, filed on August 11, 2023, and the entire contents of this Korean Patent Application are incorporated herein by reference. Background Art
[0003] Recently, secondary batteries are widely used not only in small devices such as portable electronic devices, but also in medium and large devices such as battery packs or power storage devices in hybrid vehicles or electric vehicles. In particular, in recent years, as concerns about environmental issues have increased, a large amount of research has been conducted on electric vehicles, hybrid electric vehicles, etc. that can replace vehicles using fossil fuels such as gasoline vehicles and diesel vehicles, which are the main causes of air pollution.
[0004] Conventional lithium secondary batteries are limited to short-range electric vehicles due to their energy density. Therefore, until now, technology has been developing in the direction of increasing the energy density of lithium secondary batteries.
[0005] However, lithium secondary batteries developed for automobiles have a problem of requiring a long time to charge after being discharged during vehicle operation. Therefore, as the adoption rate of electric vehicles increases, there is a growing demand to shorten the charging time to a level acceptable to users.
[0006] Meanwhile, a lithium secondary battery is an electric power generation device that can be charged and discharged through a stacked structure of a positive electrode, a separator, and a negative electrode. When a lithium secondary battery is charged, a lithium dissociation reaction is triggered at the positive electrode inside the battery, wherein the lithium contained in the positive electrode active material is oxidized and released, and a lithium insertion reaction occurs at the negative electrode, wherein the lithium is reduced and enters the negative electrode active material. Generally, the dissociation reaction in the positive electrode active material is faster than the insertion reaction in the negative electrode active material, so the fast charge and discharge performance of the lithium secondary battery is mainly determined by the negative electrode.
[0007] As the negative electrode active material, a material containing graphite is widely used. The average potential of the material containing graphite when releasing lithium is about 0.2 V (based on Li / Li +), and the discharge potential presents a relatively flat pattern. Due to this, when graphite is used as the negative electrode active material, the voltage of the secondary battery is high and has certain advantages. However, the capacitance per unit mass of the graphite material is 372 mAh / g, which is small. However, the current capacity of the graphite material has been improved to be close to the above theoretical capacity, so it is difficult to further increase the capacity. In addition, when graphite is used as the negative electrode active material, the insertion reaction of lithium ions proceeds at a slow rate, so there is a limitation that the fast charging performance is low compared to the case where other negative electrode active materials are applied.
[0008] Therefore, in order to improve the high capacity and fast charging performance of lithium secondary batteries, a variety of negative electrode active materials have been studied. For example, it was found that silicon can reversibly absorb and release a large amount of lithium by reacting with lithium compounds, and a large amount of research on this has been conducted recently. The theoretical maximum capacity of silicon is about 4020mAh / g (9800mAh / cc, specific gravity 2.23), which is significantly greater than the theoretical maximum capacity of graphite-based materials and therefore has useful advantages as a high energy density and / or high capacity negative electrode material. However, silicon causes a large volume change (about 300%) during charging and discharging, and does not have high rate discharge characteristics, and therefore has limitations in that the lifespan and fast discharge efficiency of lithium secondary batteries containing silicon are not high.
[0009] Therefore, in order to fundamentally solve such problems, negative electrode technology that can simultaneously achieve high rapid charge and discharge performance and life characteristics while improving charge and discharge capacity is highly desired. Summary of the Invention
[0010] Technical issues
[0011] An object of the present disclosure is to provide a negative electrode for a lithium secondary battery having improved rapid charge and discharge performance, enabling the secondary battery to be charged in a short time, having high charge and discharge capacity, and exhibiting excellent life characteristics, and a method for manufacturing the same.
[0012] Technical Solution
[0013] In order to solve the above problems,
[0014] The present disclosure provides a negative electrode comprising:
[0015] negative electrode current collector,
[0016] a first negative electrode active layer disposed on at least one side of the negative electrode current collector and comprising a first carbon-based negative electrode active material, and
[0017] a second negative electrode active layer disposed on the first negative electrode active layer and comprising a second carbon-based negative electrode active material and a silicon-based negative electrode active material;
[0018] The first negative electrode active layer
[0019] having an orientation index (OI) in the range of 5 to 15 according to the following formula 1 第一 )and
[0020] The following formula 2 is satisfied within the range of 0.2 to 0.6:
[0021] [Formula 1]
[0022] OI=I 004 / I 110
[0023] [Formula 2]
[0024] OI 第一 / OI 第二
[0025] In Equation 1 and Equation 2,
[0026] I 004 represents the area of the peak representing the (004) crystal plane of the carbon-based negative electrode active material in the X-ray diffraction spectrum (XRD) analysis of the negative electrode active layer,
[0027] I 110 represents the area of the peak representing the (110) crystal plane of the carbon-based negative electrode active material in the X-ray diffraction spectrum (XRD) analysis of the negative electrode active layer,
[0028] OI 第一 represents an orientation index of the first carbon-based negative electrode active material contained in the first negative electrode active layer,
[0029] OI 第二 Indicates the orientation index of the second carbon-based negative electrode active material contained in the second negative electrode active layer.
[0030] In this case, the second negative active layer may include 1 wt % to 25 wt % of the silicon-based negative active material based on the weight of the second negative active layer.
[0031] In addition, the orientation index (OI) of the first negative active layer may be in the range of 7 to 12.
[0032] In addition, the carbon-based negative active material may include one or more types of natural graphite and artificial graphite, respectively.
[0033] In addition, the silicon-based negative electrode active material may include one or more types of silicon (Si), silicon carbide (SiC), and silicon oxide (SiO q , where 0.8≤q≤2.5).
[0034] In addition, the total thickness of the first negative electrode active layer and the second negative electrode active layer may be in the range of 50 μm to 500 μm.
[0035] Furthermore, the present disclosure provides a method for manufacturing the negative electrode according to the present disclosure, comprising:
[0036] applying a negative electrode slurry to at least one side of a negative electrode current collector;
[0037] applying a magnetic field to the applied negative electrode slurry; and
[0038] The negative electrode slurry to which the magnetic field is applied is dried to form a negative electrode active layer.
[0039] In this case, the step of applying the magnetic field may be performed for a duration of 1 second to 20 seconds.
[0040] Furthermore, the step of applying a magnetic field may be performed with a magnetic field strength ranging from 1,000G to 7,000G.
[0041] Furthermore, the present disclosure provides a lithium secondary battery comprising:
[0042] an electrode assembly including a positive electrode, a negative electrode according to the present disclosure, and a separator disposed between the positive electrode and the negative electrode; and
[0043] The electrolyte composition impregnates the electrode assembly.
[0044] The positive electrode may include a positive electrode active layer disposed on at least one side of a positive electrode current collector and including one or more types of lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2:
[0045] [Chemical Formula 1]
[0046] Li x [Ni y Co z Mn w M 1 v ]O2
[0047] [Chemical Formula 2]
[0048] LiM 2 p Mn 1-p O4
[0049] In the above Chemical Formula 1 and Chemical Formula 2,
[0050] M 1 is one or more types of elements as follows: W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo,
[0051] x, y, z, w, and v are respectively 1.0 ≤ x ≤ 1.30, 0.5 ≤ y < 1, 0 < z ≤ 0.3, 0 < w ≤ 0.3, and 0 ≤ v ≤ 0.1, and y + z + w + v = 1,
[0052] M 2 is Ni, Co, or Fe,
[0053] p is 0.05 ≤ p ≤ 1.0.
[0054] Specifically, the positive electrode active material may include one or more types of the following: LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2, LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, LiNi 0.7 Mn 1.3 O4, LiNi 0.5 Mn 1.5 O4, and LiNi 0.3 Mn 1.7 O4.
[0055] In addition, the electrode assembly may be a stacked electrode assembly, a Z-shaped electrode assembly, or a Z-stack electrode assembly.
[0056] Beneficial effects
[0057] The negative electrode for a lithium secondary battery according to one aspect of the present disclosure has the characteristics of high charge and discharge capacity and excellent life characteristics. In addition, the lithium secondary battery including the negative electrode has the advantages of having excellent output characteristics and being able to be charged in a short time even at a 1C rate. DETAILED DESCRIPTION
[0058] The present disclosure is susceptible to various modifications and various embodiments, and thus specific embodiments thereof will be described in detail below.
[0059] However, it should be understood that the present disclosure is not limited to specific embodiments, but includes all modifications, equivalents, or substitutes within the spirit and technical scope of the present disclosure.
[0060] The terms "include", "comprising" and "having" used herein indicate the presence of features, numbers, steps, actions, parts or components or a combination thereof described in the specification, and it should be understood that they do not preclude the possibility of the presence or addition of one or more other features, numbers, steps, actions, parts, components or a combination thereof.
[0061] Furthermore, in the present disclosure, when a portion of a layer, film, region, plate, or the like is disposed "on" another portion, this includes not only a case where the portion is "directly disposed on" another portion but also a case where another portion is interposed therebetween. Conversely, when a portion of a layer, film, region, plate, or the like is disposed "below" another portion, this includes not only a case where the portion is "directly disposed below" another portion but also a case where another portion is interposed therebetween. Furthermore, in the present application, "on..." includes not only a case where the portion is disposed on an upper portion but also a case where the portion is disposed on a lower portion.
[0062] In addition, in the disclosure, "comprising as a main component" may mean, relative to the total weight (or total volume), comprising at least 50% by weight (or at least 50% by volume), at least 60% by weight (or at least 60% by volume), at least 70% by weight (or at least 70% by volume), at least 80% by weight (or at least 80% by volume), at least 90% by weight (or at least 90% by volume), or at least 95% by weight (or at least 95% by volume) of the defined component. For example, "comprising graphite as a main component as a negative electrode active material" may mean, based on the total weight of the negative electrode active material, comprising at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or at least 95% by weight of graphite, and in some cases may mean that the entire negative electrode active material is graphite, comprising at least 100% by weight of graphite.
[0063] In addition, as used herein, “orienting the carbon-based negative electrode active material” or “aligning the carbon-based negative electrode active material” means arranging certain crystal planes (e.g., the ab-axis crystal plane of graphite) representing the two-dimensional planar structure of the carbon-based negative electrode active material containing the negative electrode active material particles to have a predetermined slope based on the surface of the negative electrode current collector, which may be different from the carbon-based negative electrode active material particles themselves being arranged in a specific direction within the negative electrode active layer.
[0064] In addition, the term "highly oriented carbon-based negative electrode active material" may refer to a situation in which a specific crystal plane (e.g., the ab-axis crystal plane of graphite) of the two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer has a high frequency of having a predetermined slope based on the surface of the negative electrode current collector. In addition, in some cases, it may refer to a situation in which the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer is arranged at a high angle (e.g., a near-vertical angle, greater than 45°, more specifically, greater than 60°) based on the surface of the negative electrode current collector.
[0065] In addition, the “high orientation index (OI) of the carbon-based negative electrode active material” may mean that the “orientation index (OI)” referred to herein has a large value, so that certain crystal planes representing the two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer (for example, the ab axis crystal plane of graphite) are aligned at a low angle (for example, less than 45°) based on the surface of the negative electrode current collector. Conversely, the “low orientation index (OI) of the carbon-based negative electrode active material” may mean that the “orientation index (OI)” has a small value, so that the crystal planes of the carbon-based negative electrode active material contained in the negative electrode active layer are aligned at a high angle (for example, a near-vertical angle of 45° or greater, specifically, 60° or greater) based on the surface of the negative electrode current collector.
[0066] In addition, as used herein, the term "crystal plane of carbon-based negative active material" may refer to a surface where the atoms of the carbon-based negative active material form a crystal shape, which in the present disclosure may mean a crystal plane including a plane of the carbon-based negative active material, or a crystal plane including the a-axis / b-axis / ab-axis of the carbon-based negative active material crystal.
[0067] Furthermore, as used herein, “average particle diameter (D 50 The term "mean diameter" refers to a particle diameter at which the sum of the values in the particle diameter distribution of the particles is 50%, which is also referred to as a median diameter. The average particle diameter can be measured by a method generally known in the art. For example, the average particle diameter can be measured using a particle size analyzer or an analyzer based on laser diffraction particle size distribution measurement.
[0068] Hereinafter, the present disclosure will be described in more detail.
[0069] Negative electrode for lithium secondary battery
[0070] The present disclosure provides a negative electrode for a lithium secondary battery, comprising:
[0071] negative electrode current collector,
[0072] a first negative electrode active layer disposed on at least one side of the negative electrode current collector and comprising a first carbon-based negative electrode active material, and
[0073] a second negative electrode active layer disposed on the first negative electrode active layer and comprising a second carbon-based negative electrode active material and a silicon-based negative electrode active material;
[0074] The first negative electrode active layer
[0075] having an orientation index (OI) in the range of 5 to 15 according to the following formula 1 第一 )and
[0076] The following formula 2 is satisfied within the range of 0.2 to 0.6:
[0077] [Formula 1]
[0078] OI=I 004 / I 110
[0079] [Formula 2]
[0080] OI 第一 / OI 第二
[0081] In Equation 1 and Equation 2,
[0082] I 004 represents the area of the peak representing the (004) crystal plane of the carbon-based negative electrode active material in the X-ray diffraction spectrum (XRD) analysis of the negative electrode active layer,
[0083] I 110 represents the area of the peak representing the (110) crystal plane of the carbon-based negative electrode active material in the X-ray diffraction spectrum (XRD) analysis of the negative electrode active layer,
[0084] OI 第一 represents an orientation index of the first carbon-based negative electrode active material contained in the first negative electrode active layer,
[0085] OI 第二 Indicates the orientation index of the second carbon-based negative electrode active material contained in the second negative electrode active layer.
[0086] The negative electrode for a lithium secondary battery according to one aspect of the present disclosure includes a negative electrode active layer on at least one side of a negative electrode current collector. The negative electrode active layer is a layer that realizes the electroactivity of the negative electrode and contains a negative electrode active material as a main component that realizes the electrochemical redox reaction during the charge and discharge of the battery. The negative electrode active material includes a carbon-based negative electrode active material and a silicon-based negative electrode active material.
[0087] Here, the carbon-based negative electrode active material refers to a material having carbon atoms as a main component. Such a carbon-based negative electrode active material may include graphite.
[0088] Graphite may include any one or more of natural graphite and artificial graphite. In addition, in addition to natural graphite and artificial graphite, graphite may also include mesophase calcined carbon (blocky mesophase) derived from tar and pitch, graphitized coke (raw coke, green coke, pitch coke, needle coke, petroleum coke, etc.), etc.
[0089] For example, the negative electrode active layer according to one aspect of the present disclosure may solely contain artificial graphite. The present disclosure includes artificial graphite solely in the negative electrode active layer, which significantly improves the lifespan of the negative electrode, which can be advantageous in conditions where the negative electrode must withstand frequent charging for long periods of time, such as in automotive batteries. Furthermore, compared to natural graphite, artificial graphite has the advantages of facilitating rapid charging and excellent output performance.
[0090] In addition, the negative electrode active layer according to one aspect of the present disclosure may contain both natural graphite and artificial graphite. In this case, the mixing ratio of natural graphite and artificial graphite may be 5% to 50% by weight: 50% to 95% by weight, 20% to 45% by weight: 55% to 80% by weight, or 5% to 15% by weight: 85% to 95% by weight, based on weight. The present disclosure can maintain high fast charging speed and output performance by simultaneously containing natural graphite and artificial graphite in the negative electrode active layer at the above content ratio.
[0091] In addition, the carbon-based negative electrode active material may have a round particle shape rather than a shape such as a plate shape, a sheet shape, a flake shape, a needle shape, etc. Here, the round particle shape may refer to a particle having a non-angular shape. When performing a cross-sectional structural analysis or when projecting into a two-dimensional particle, such a particle may have a spherical or elliptical shape, and in some cases, may have an amorphous shape when the shape is difficult to define.
[0092] For example, the carbon-based negative electrode active material can be graphite having a spherical particle shape. In this case, the spherical particles can be processed to have a spherical shape / form during manufacturing, or can be a spherical flake graphite assembly formed by the aggregation of multiple flake graphites. If the spherical particles are an assembly, one graphite assembly can be formed by the aggregation of 2 to 100, preferably 3 to 20, flake graphites. The present disclosure can further increase the conductivity of the negative electrode active layer by controlling the shape of the carbon-based negative electrode active material as described above, and can improve the adhesion between the negative electrode active layer and the negative electrode current collector by maximizing the contact area with the negative electrode current collector.
[0093] Furthermore, the carbon-based negative electrode active material can be in the form of an ellipsoid. In this case, it is easier to ensure that the carbon-based negative electrode active material serves as a lithium ion transport path in the negative electrode active layer, thereby enabling charging to be completed in a shorter time even under the same charging conditions.
[0094] In addition, the size of the carbon-based negative electrode active material can be adjusted to a certain range. Specifically, the average particle diameter (D 50 ) can be in the following range: 1μm to 30μm, specifically, 1μm to 20μm, 1μm to 15μm, 1μm to 10μm, 1μm to 8μm, 1μm to 5μm, 1μm to 3μm, 10μm to 20μm, 11μm to 19μm, 8μm to 15μm, 15μm to 20μm, 13μm to 19μm, 14μm to 17μm, 5μm to 8μm, 7μm to 14μm, 9μm to 13μm, 2μm to 6μm, 5μm to 9μm, 1μm to 4.5μm, or 1μm to 3μm.
[0095] The present disclosure can control the average particle diameter of the carbon-based negative electrode active material within the above range, thereby easily suppressing the increase in the resistance of the negative electrode active layer. In addition, within the above average particle diameter range, the carbon-based negative electrode active material can increase the specific surface area per unit weight while maximizing the degree of disorder of each particle in the expansion direction, so as to prevent the particles from expanding due to the charging of lithium ions, thereby further improving the adhesion between the negative electrode active layer and the negative electrode current collector. In addition, the carbon-based negative electrode active material has the advantage of ensuring the transmission path of lithium ions within the average particle diameter range, thereby further improving the fast charging performance. However, when the particle diameter of the carbon-based negative electrode active material is lower than the average particle diameter (D 50 ) is less than the lower limit value, a large amount of binder is required due to the increase in the number of particles per unit volume, and thus the electrical characteristics of the negative electrode active layer containing them may be deteriorated. On the other hand, when the average particle diameter (D 50) may significantly increase the expansion rate of the negative electrode active material during charging and discharging of the secondary battery, so that the binding characteristics of the negative electrode active material particles and the binding characteristics of the negative electrode active material particles and the negative electrode current collector may be reduced with repeated charging and discharging, thereby significantly reducing the cycle characteristics.
[0096] In addition, the silicon-based negative electrode active material refers to a material having silicon atoms as a main component. Such silicon-based negative electrode active materials include silicon (Si), silicon carbide (SiC), silicon monoxide (SiO) or silicon dioxide (SiO2), etc., which can be contained in the negative electrode active layer alone or in combination. When the silicon-based negative electrode active materials silicon monoxide (SiO) and silicon dioxide (SiO2) are uniformly mixed or composited and contained in the negative electrode active layer, they can be expressed as silicon oxide (SiO q , where 0.8≤q≤2.5).
[0097] In addition, the silicon-based negative electrode active material may be doped or alloyed with Li, Mg, Al, Ca, or Ti, etc. In addition, the silicon-based negative electrode active material may be surface-treated with a carbon coating or the like on the surface in order to suppress volume expansion during charging when oxygen (O) is contained, while also improving the conductivity of the negative electrode active material.
[0098] In addition, the size of the silicon-based negative electrode active material can be adjusted within a certain range. Specifically, the average particle diameter (D 50 ) can be in the following range: 0.5μm to 20μm, more specifically, 0.5μm to 15μm, 0.5μm to 13μm, 0.5μm to 9μm, 0.5μm to 6μm, 0.5μm to 4μm, 0.5μm to 2μm, 9μm to 18μm, 10μm to 17μm, 7μm to 14μm, 14μm to 18μm, 12μm to 18μm, 11μm to 15μm, 4μm to 8μm, 4μm to 13μm, 5μm to 12μm, 7μm to 11μm, 1μm to 5μm, 3μm to 8μm, 1μm to 3μm, or 1μm to 2μm.
[0099] At the same time, the negative electrode active layer may have a double-layer structure in which a first negative electrode active layer and a second negative electrode active layer are sequentially stacked on a negative electrode current collector. Since the double-layer structure of the negative electrode active layer makes it easy to control the composition of each layer, the performance of the negative electrode can be improved by controlling the type or content of the components contained in each layer according to a specific purpose, such as improving the energy efficiency of the battery or improving the adhesion between the active layer and the current collector. For example, the negative electrode active layer may selectively include a silicon-based negative electrode active material having a high battery charge and discharge capacity only in the first negative electrode active layer in contact with the negative electrode current collector. In addition, the negative electrode active layer may selectively include natural graphite or the like having good adhesion as a negative electrode active material only in the first negative electrode active layer in contact with the negative electrode current collector, or may include a high content of a binder having adhesion properties with the components constituting the active layer.
[0100] The present disclosure includes a first carbon-based negative electrode active material in the first negative electrode active layer and a second carbon-based negative electrode active material and a silicon-based negative electrode active material in the second negative electrode active layer. In this case, the first carbon-based negative electrode active material and the second carbon-based negative electrode active material included in each negative electrode active layer may be the same or different in type and / or content.
[0101] The present disclosure may include a silicon-based negative electrode active material in the second negative electrode active layer adjacent to the positive electrode active layer to increase the charge and discharge capacity of the negative electrode. In addition, by including a silicon-based negative electrode active material in the second negative electrode active layer that is not adjacent to the negative electrode current collector, the present disclosure may prevent the problem of reduced adhesion between the negative electrode active layer and the negative electrode current collector due to volume changes of the silicon-based negative electrode active material during charge and discharge of the secondary battery. In addition, the silicon-based negative electrode active material may be implemented so that the orientation index (OI) of the first negative electrode active layer is 1.5-2.0. 第一 ) is relatively lower than the orientation index (OI) of the second negative electrode active layer 第二 Such a trend of the orientation index within the entire negative electrode active layer can significantly increase the lithium mobility within the negative electrode active layer, which has the advantage of providing good initial lithium mobility during charge and discharge, thereby shortening the charge and discharge time of the secondary battery at a low charge rate.
[0102] The silicon-based negative electrode active material may be included in an amount of 1% to 25% by weight based on the total weight of the total negative electrode active material included in the second negative electrode active layer. Specifically, the silicon-based negative electrode active material may be included in an amount of 5% to 25% by weight; 9% to 23% by weight; 10% to 20% by weight; 8% to 18% by weight; 5% to 15% by weight; 8% to 13% by weight; 11% to 23% by weight; 15% to 20% by weight; 11% to 19% by weight; 19% to 25% by weight; or 18% to 23% by weight based on the total weight of the total negative electrode active material. The present disclosure can adjust the content ratio of the silicon-based negative electrode active material in the negative electrode active material to the above range, thereby minimizing the volume change rate caused by the silicon-based negative electrode active material during charge and discharge, thereby maintaining the lithium transport path of the carbon-based negative electrode active material in the negative electrode active layer due to the application of the magnetic field. Therefore, the negative electrode according to one aspect of the present disclosure can significantly improve lifespan characteristics while achieving a high charge capacity, and can significantly shorten the charge speed of the secondary battery.
[0103] In addition, the negative electrode according to one aspect of the present disclosure can control the crystal structure characteristics of the carbon-based negative electrode active material contained in the negative electrode active layer to achieve a fast charging speed. Specifically, the orientation index (OI) of the carbon-based negative electrode active material of the first negative electrode active layer according to the following formula 1 is: 第一 ) can be in the range of 5 to 15:
[0104] [Formula 1]
[0105] OI=I 004 / I 110
[0106] In formula 1,
[0107] I 004 represents the area of the peak representing the (004) crystal plane of the carbon-based negative electrode active material in the X-ray diffraction spectrum (XRD) analysis of the negative electrode active layer,
[0108] I 110 It represents the area of the peak representing the (110) crystal plane of the carbon-based negative electrode active material in the X-ray diffraction spectrum (XRD) analysis of the negative electrode active layer.
[0109] The orientation index (OI) of a carbon-based negative electrode active material when measured by X-ray diffraction (XRD) can be an indicator of the degree to which the ab-axis crystal plane of the carbon-based negative electrode active material is oriented in a certain direction (specifically, relative to the surface of the negative electrode current collector). Specifically, for a carbon-based negative electrode active material, i.e., graphite, the negative electrode active layer shows peaks of 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2° in X-ray diffraction measurement. This shows the (002) plane, (100) plane, (101) R plane, (101) H plane, (004) plane, and (110) plane of graphite. Here, the peak shown at 2θ=43.4±0.2° can be regarded as an overlap of peaks corresponding to the (101)R plane of the carbon-based negative active material and the (111) plane of the current collector (eg, copper (Cu)).
[0110] Among them, the orientation index (OI) of the carbon-based negative active material can be measured by the ratio of the areas obtained by integrating the respective intensities of the peak representing the (004) plane at 2θ = 54.7 ± 0.2° and the peak representing the (110) plane at 2θ = 77.5 ± 0.2°.
[0111] Since the peak at 2θ = 54.7 ± 0.2° is a peak indicating a crystal plane of a carbon-based negative electrode active material having an inclination relative to the negative electrode current collector, the orientation index (OI) of the carbon-based negative electrode active material can mean that a value closer to 0 means that the inclination relative to the surface of the negative electrode current collector is closer to 90°, and a larger value means that the inclination relative to the surface of the negative electrode current collector is closer to 0° or 180°. In other words, the first negative electrode active layer according to one aspect of the present disclosure can be aligned so that the carbon-based negative electrode active material contained in the layer has an angle of 60° or greater, 70° or greater, 70° to 90°, 80° to 90°, 65° to 85°, or 70° to 85° relative to the negative electrode current collector. Therefore, the orientation index (OI) of the carbon-based negative electrode active material of the first negative electrode active layer can be lower than when the carbon-based negative electrode active material is aligned at a lower angle of less than 60°. Here, the orientation index (OI) can represent the degree to which the carbon-based negative electrode active material particles are aligned on the surface of the negative electrode current collector. In addition, in some cases, the orientation index (OI) represents the degree of alignment of the ab-axis crystal plane of the carbon-based negative electrode active material in the negative electrode active layer. In addition, the alignment of the ab-axis crystal plane of the carbon-based negative electrode active material can also cause the rotation of the carbon-based negative electrode active material particles contained in the negative electrode active layer. However, since the rotation of the particles in this case is affected by the shape of the particles, it is not equivalent to the degree to which the ab-axis crystal plane is aligned, and the above orientation index (OI) may be difficult to represent the alignment of the carbon-based negative electrode active material particles.
[0112] Here, the orientation index (OI) of the first carbon-based negative electrode active material included in the first negative electrode active layer is 第一 ) can be in the range of 5 to 15, more specifically in the range of 5 to 13, 5 to 11, 5 to 9, 7 to 15, 10 to 15, 7 to 12, 7.5 to 10, 6 to 9.5, or 7.5 to 9.5.
[0113] When the orientation index (OI 第一 ) is less than the above lower limit, the adhesion to the negative electrode current collector may be reduced. Therefore, the present disclosure improves the orientation index (OI) of the carbon-based negative electrode active material contained in the first negative electrode active layer by 第一 ) is adjusted to a value equal to or greater than the above lower limit, since the ratio of the crystal planes of the carbon-based negative electrode active material molecules constituting the negative electrode active material particles facing the negative electrode current collector is increased, the fast charging performance of the negative electrode can be improved to the extent that the adhesion between the first negative electrode active layer and the negative electrode current collector is not reduced. In addition, by adjusting the orientation index (OI) of the carbon-based negative electrode active material contained in the negative electrode active layer to a value equal to or greater than the above lower limit, the fast charging performance of the negative electrode can be improved to the extent that the adhesion between the first negative electrode active layer and the negative electrode current collector is not reduced. 第一) is adjusted to be equal to or less than the above upper limit, the present disclosure can ensure an ion migration channel within the negative electrode active layer in which lithium ions can migrate over a relatively short distance. Therefore, the negative electrode of the present disclosure can prevent the increase in resistance caused by the long migration distance of lithium ions, and thus can further increase the migration speed of lithium ions during charging and discharging, thereby simultaneously improving fast charging performance and output performance with high safety.
[0114] In addition, the first negative electrode active layer may satisfy Formula 2 in the range of 0.2 to 0.6:
[0115] [Formula 2]
[0116] OI 第一 / OI 第二
[0117] In formula 2,
[0118] OI 第一 represents an orientation index of the first carbon-based negative electrode active material contained in the first negative electrode active layer,
[0119] OI 第二 Indicates the orientation index of the second carbon-based negative electrode active material contained in the second negative electrode active layer.
[0120] Formula 2 represents the orientation index (OI) of the first carbon-based negative electrode active material contained in the first negative electrode active layer. 第一 ) and the orientation index (OI 第二 ) ratio.
[0121] The second negative electrode active material layer may also include a silicon-based negative electrode active material in addition to the first carbon-based negative electrode active material, and when it is aligned and / or oriented according to the application of a magnetic field, it may affect the alignment and / or orientation of the first carbon-based negative electrode active material. Therefore, the first negative electrode active layer and the second negative electrode active layer may have an orientation index ratio within a predetermined range to satisfy the above formula 2. Specifically, the first negative electrode active layer may satisfy formula 2 in the range of 0.2 to 0.6. For example, the first negative electrode active layer may satisfy the range of 0.2 to 0.5, 0.25 to 0.5, 0.3 to 0.5, 0.2 to 0.4, 0.4 to 0.6, 0.25 to 0.45, or 0.3 to 0.45. The first negative electrode active layer of the present disclosure may be characterized in that, by satisfying the above formula 2 within the above range, a shortened lithium transmission path can be established inside the first negative electrode active layer, so that the charging rate of the secondary battery can be increased even at a low charging rate of 1C, and the life of the negative electrode can be increased.
[0122] Specifically, conventionally, fast charging of lithium secondary batteries is performed by a constant current-constant voltage (CC-CV) charging method, which increases the rate by charging under high charge rate conditions exceeding 1C rate. Generally, in the constant current-constant voltage (CC-CV) charging method, the diffusion of lithium ions in the electrode during charging occurs during the constant current (CC) charging step, which inevitably causes concentration polarization due to the long diffusion period. Such concentration polarization of lithium ions easily leads to lithium precipitation at the negative electrode, especially under high rate conditions where the charging current (A) exceeds the standard value (in other words, the current at 1C rate: 1A) compared to the rated capacity value (Ah) of the secondary battery, which has the limitation of significantly reducing the safety of the secondary battery. In addition, the high rate constant current-constant voltage (CC-CV) charging method reaches the upper limit value at a very fast rate during the constant current (CC) charging stage, so that the current may drop to the preset limit value before the active material is completely consumed. In other words, during the constant voltage (CV) charging stage, the charging time is significantly increased, so that the effect of reducing the total time for charging the secondary battery is insignificant.
[0123] However, the present disclosure can ensure that the ion migration channel of lithium ions in the negative electrode active layer is shorter, and thus the resistance caused in the negative electrode active layer during charging can be significantly reduced. When charging is performed by a constant current-constant voltage (CC-CV) charging method, such a reduction in resistance can make it possible for the time for performing the constant current (CC) charging step to be longer than the time for performing the constant voltage (CV) charging step during the entire charging time. Here, the constant current (CC) charging step has the same charging capacity per unit time due to the same amount of current flowing, but the constant voltage (CV) charging step shows a trend of decreasing current in order to maintain the same voltage. In other words, the charging capacity per unit time in the constant voltage (CV) charging step is sharply reduced, so that the entire charging time can be significantly reduced as the constant current (CC) charging step is performed for an increased time. Therefore, the present disclosure achieves this by controlling the orientation index (OI) of the carbon-based negative electrode active material. 第二 ), the time for which the constant current (CC) charging step is performed can be increased, thereby enabling the charging of the secondary battery to be completed in a significantly shorter time.
[0124] In addition, since such secondary batteries can be fast charged under standard value conditions (e.g., 1C rate) rather than high rate C rate conditions, it is beneficial to overcome the safety issues caused by the concentration polarization phenomenon of lithium ions induced in the negative electrode active layer during charging of lithium secondary batteries.
[0125] Meanwhile, the first negative active layer and the second negative active layer may each have a porosity within a range of 20% to 30%, and more specifically, may have a porosity within a range of 23% to 30%; 25% to 30%; 26% to 29%; or 24% to 28%.
[0126] In addition, the first negative electrode active layer and the second negative electrode active layer may have a 2 The BET specific surface area can be within the range of 0.615 m / g or less, and more specifically, can be within the range of 0.615 m / g or less. 2 / g or less, 0.6m 2 / g or less, 0.5m 2 / g or less, 0.20m 2 / g to 0.62m 2 / g, 0.30m 2 / g to 0.62m 2 / g, 0.40m 2 / g to 0.62m 2 / g, 0.40m 2 / g to 0.60m 2 / g, 0.40m 2 / g to 0.55m 2 / g, 0.40m 2 / g to 0.50m 2 / g, or 0.58m 2 / g to 0.62m 2 / g.
[0127] Here, the porosity and specific surface area can be measured by the Brunauer-Emmett-Teller (BET) method. For example, they can be measured by a BET six-point method using a porosity analyzer (Bell Japan Inc, Belsorp-II mini) by a nitrogen adsorption distribution method.
[0128] The present disclosure can further improve the energy density of the negative electrode without deteriorating the electrolyte wettability of each negative electrode active layer by adjusting the porosity and BET specific surface area of each negative electrode active layer to the above ranges.
[0129] In addition, the total thickness of the first negative electrode active layer and the second negative electrode active layer can be in the range of 50 μm to 500 μm, more specifically in the range of 100 μm to 400 μm; 200 μm to 350 μm; 50 μm to 180 μm; 80 μm to 150 μm; 100 μm to 250 μm; 200 μm to 290 μm; or 130 μm to 190 μm.
[0130] The present disclosure can achieve a high charge and discharge capacity of the negative electrode by adjusting the total thickness of the active layer of the negative electrode to the above range. In addition, it is advantageous that the volume change of the negative electrode during charging and discharging of the secondary battery can be minimized, thereby improving the life characteristics of the negative electrode.
[0131] Furthermore, the negative electrode active layer according to one aspect of the present disclosure may further selectively include a conductive material, a binder, other additives, and the like as needed, in addition to the negative electrode active material as a main component.
[0132] The conductive material may include one or more of carbon black, acetylene black, Ketjen black, carbon nanotubes, carbon fibers, etc., but is not limited thereto.
[0133] As an example, the negative electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, etc. as the conductive material, alone or in combination.
[0134] In this case, the content of the conductive material may be 0.1 to 10 parts by weight, more specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, 2 to 6 parts by weight, or 0.5 to 2 parts by weight, based on 100 parts by weight of the entire negative electrode active layer. The present disclosure can control the content of the conductive material within the range as described above, thereby preventing the following problems: the problem in which the resistance of the negative electrode increases due to a low content of the conductive material, thereby reducing the charge capacity, the problem in which the content of the negative electrode active material decreases due to an excessive amount of the conductive material, thereby reducing the charge capacity, or the problem in which the fast charge characteristics decrease due to an increased load on the negative electrode active layer.
[0135] In addition, the binder as a component that helps to bind the negative electrode active material and the conductive material to the current collector can be appropriately applied to the extent that the electrical properties of the electrode are not deteriorated, and specifically, it can include any one or more selected from the following: vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile and polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR) and fluorinated rubber.
[0136] Based on a total of 100 parts by weight of the negative electrode active layer, the content of the binder may be 0.1 to 10 parts by weight, more specifically, 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight. The present disclosure can control the content of the binder contained in the negative electrode active layer to the above range, thereby preventing the adhesiveness of the active layer from being degraded due to a low content of the binder, or preventing the electrical characteristics of the electrode from being degraded due to an excessive amount of the binder.
[0137] In addition, the negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, nickel, titanium, calcined carbon, etc. can be used. In the case of copper or stainless steel, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can also be used. In addition, considering the conductivity and total thickness of the negative electrode to be manufactured, the average thickness of the negative electrode current collector can be appropriately applied to be 1 μm to 500 μm.
[0138] lithium secondary batteries
[0139] Furthermore, in one embodiment, the present disclosure provides a lithium secondary battery comprising:
[0140] an electrode assembly comprising a positive electrode, the negative electrode of the present disclosure, and a separator disposed between the positive electrode and the negative electrode; and
[0141] The electrolyte composition impregnates the electrode assembly.
[0142] A lithium secondary battery according to one aspect of the present disclosure includes an electrode assembly having a structure in which a plurality of positive electrodes and a plurality of negative electrodes are alternately arranged with a separator therebetween. The lithium secondary battery includes the negative electrode of the present disclosure as described above and has a large charge and discharge capacity, excellent lifespan characteristics, and can be charged in a short time even at a 1C rate, and can therefore be usefully used as a power source for medium and large-sized devices such as electric vehicles.
[0143] In this case, the negative electrode has the same configuration as that described above, and thus a detailed description is omitted.
[0144] In addition, the positive electrode includes a positive electrode active layer containing a positive electrode active material on a positive electrode current collector, and the positive electrode active layer may selectively further contain a conductive material, a binder, other additives, etc. as needed.
[0145] The positive electrode active material, as a material capable of undergoing an electrochemical reaction on a positive electrode current collector, may include one or more of lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2, which are capable of reversibly intercalating and deintercalating lithium ions:
[0146] [Chemical Formula 1]
[0147] Li x [Ni y Co z Mn w M 1 v O2
[0148] [Chemical Formula 2]
[0149] LiM 2 p Mn q P r O4
[0150] In the above Chemical Formula 1 and Chemical Formula 2,
[0151] M 1 is one or more types of elements selected from the following: W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.
[0152] [[ID=·]](38) x, y, z, w, and v are respectively 1.0 ≤ x ≤ 1.30, 0.5 ≤ y < 1, 0 < z ≤ 0.3, 0 < w ≤ 0.3, and 0 ≤ v ≤ 0.1, and y + z + w + v = 1,
[0153] M 2 is Ni, Co, or Fe.
[0154] p is 0.05 ≤ p ≤ 1.0.
[0155] q is 2 - p.
[0156] r is 0 or 1.
[0157] The lithium metal oxides represented by Chemical Formula 1 and Chemical Formula 2 are materials containing high contents of nickel (Ni) and manganese (Mn), respectively, and when used as the positive electrode active material, compared with the conventionally used positive electrode active material such as lithium iron phosphate (LiFeO4), it has the advantage of being able to stably supply high-capacity and / or high-voltage electric power.
[0158] In this case, the lithium metal oxide represented by the above Chemical Formula 1 may include LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi[[ID=<>]] 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 [[ID=<>]]Co 0.05 Mn 0.05 …… O2, LiNi0.6 Co 0.2 Mn 0.1 Al 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2、LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, etc., and the lithium metal oxide represented by the above Chemical Formula 2 may include LiNi 0.7 Mn 1.3 O4、LiNi 0.5 Mn 1.5 O4、LiNi 0.3 Mn 1.7 O4, etc., these can be used alone or in combination.
[0159] In addition, the positive electrode active material may be included in an amount of 85 parts by weight or more, more specifically 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more, based on 100 parts by weight of the positive electrode active layer.
[0160] Furthermore, the positive electrode active layer may further contain a conductive material, a binder, other additives, and the like in addition to the positive electrode active material.
[0161] In this case, the conductive material for improving the electrical properties of the positive electrode can be any conductive material conventionally used in the art, but can specifically include at least one or more selected from the following: natural graphite, artificial graphite, carbon black, acetylene black, denka black, Ketjen black, super-P, channel black, furnace black, lamp black, thermal black, graphene and carbon nanotubes.
[0162] In addition, the conductive material may be included in an amount of 0.1 to 5 parts by weight, more specifically 0.1 to 4 parts by weight, 2 to 4 parts by weight, 1.5 to 5 parts by weight, 1 to 3 parts by weight, 0.1 to 2 parts by weight, or 0.1 to 1 part by weight, based on 100 parts by weight of each positive electrode active layer.
[0163] In addition, the binder plays a role in binding the positive electrode active material, the positive electrode additive and the conductive material to each other, and it can be used without particular limitation as long as it has such an effect. Specifically, the binder may include one or more types of resins selected from the following: polyvinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate, and copolymers thereof. As an example, the binder may include polyvinylidene fluoride.
[0164] In addition, the binder may be included in an amount of 1 to 10 parts by weight, more specifically, 2 to 8 parts by weight or 1 to 5 parts by weight, based on 100 parts by weight of the positive active layer.
[0165] The total thickness of the positive electrode active layer is not particularly limited, but may be within the range of 50 to 300 μm, more specifically 100 to 200 μm, 80 to 150 μm, 120 to 170 μm, 150 to 300 μm, 200 to 300 μm, or 150 to 190 μm.
[0166] In addition, the positive electrode can use a positive electrode current collector with high conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. can be used. In the case of aluminum or stainless steel, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, considering the conductivity and total thickness of the positive electrode to be manufactured, the average thickness of the current collector can be appropriately applied to be 3μm to 500μm.
[0167] In addition, the separator interposed between the positive electrode and the negative electrode of each unit cell is an insulating film with high ion permeability and mechanical strength, and can be any polymer conventionally used in the art, but is not particularly limited thereto, and can include one or more types of polymers such as chemically resistant and hydrophobic polypropylene, polyethylene, and polyethylene-propylene copolymer. The separator can have the form of a porous polymer base substrate containing the above-mentioned polymer, such as a sheet or a non-woven fabric, and in some cases, it can also have the form of a composite separator in which organic particles or inorganic particles are coated on the porous polymer base substrate by an organic binder. In addition, the average diameter of the pores of the separator can be 0.01 μm to 10 μm and the average thickness of the separator can be 5 μm to 300 μm.
[0168] Meanwhile, the lithium secondary battery according to one aspect of the present disclosure may be in the form of a secondary battery that may include a stacked electrode assembly, a Z-shaped electrode assembly, or a Z-stacked electrode assembly, but is not particularly limited thereto. As an example, the lithium secondary battery according to one aspect of the present disclosure may be a pouch-type secondary battery or a prismatic secondary battery.
[0169] The pouch-type secondary battery and / or the prismatic secondary battery has a highly exploitable advantage in terms of energy density because unit cells of the secondary battery can be packed with high density within a limited space.
[0170] Furthermore, in the lithium secondary battery, the electrolyte composition may be used without particular limitation as long as it is conventionally used in lithium secondary batteries.
[0171] Specifically, the electrolyte composition may include a non-aqueous organic solvent, a lithium salt, an electrolyte additive, and the like.
[0172] Here, the non-aqueous organic solvent can be any organic solvent known in the art for non-aqueous electrolytes without particular limitation. For example, the non-aqueous organic solvent includes N-methyl-2-pyrrolidone, ethylene carbonate (EC), propylene carbonate (PC), propylene carbonate, butylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), γ-butyrolactone, 1,2-dimethoxyethane (DME), tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl pyrophosphate (MP), ethyl propionate (EP), propyl propionate (PP), and other non-amphoteric organic solvents can be used.
[0173] In addition, one type of non-aqueous organic solvent used in the present disclosure can be used alone, and two or more types can be mixed in any combination or ratio suitable for use. Among them, from the perspective of electrochemical stability to redox and for heat or chemical stability with solute reaction, it is particularly preferred to mix propylene carbonate, ethylene carbonate, fluoroethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, etc.
[0174] In addition, the lithium salt can be applied to any non-aqueous electrolyte known in the art without particular limitation. Specifically, the lithium salt can include one or more of the following types: LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi and (FSO2)2NLi.
[0175] The lower limit of the range of suitable concentrations of lithium salts is 0.5 mol / L or greater, more specifically 0.7 mol / L or greater, more specifically 0.9 mol / L or greater, and the upper limit is 2.5 mol / L or less, specifically 2.0 mol / L or less, more specifically 1.5 mol / L or less. When the concentration of the lithium salt is lower than 0.5 mol / L, there is a possibility that the cycle characteristics and output characteristics of the non-aqueous electrolyte battery may deteriorate due to reduced ion conductivity. In addition, if the concentration of the lithium salt exceeds 2.5 mol / L, the viscosity of the electrolyte of the non-aqueous electrolyte battery increases, which may also reduce ion conductivity, thereby possibly reducing the cycle characteristics and output characteristics of the non-aqueous electrolyte battery.
[0176] In addition, if a large amount of lithium salt is dissolved in a non-aqueous organic solvent at one time, the temperature of the electrolyte may increase due to the heat of dissolution of the lithium salt. In the case of a fluorine-containing lithium salt, if the temperature of the non-aqueous organic solvent increases significantly due to the heat of dissolution of the lithium salt, decomposition may be promoted and hydrogen fluoride (HF) may be produced. Hydrogen fluoride (HF) is undesirable because it can cause battery performance to deteriorate. Therefore, the temperature at which the lithium salt is dissolved in the non-aqueous organic solvent is not particularly limited, but can be controlled at -20°C to 80°C, more specifically at 0°C to 60°C.
[0177] In addition, electrolyte additives can be included as additional auxiliary components to improve the characteristics of the electrolyte composition. Any commonly used electrolyte additive can be added to the non-aqueous electrolyte of the present disclosure in any proportion. Specifically, compounds with overcharge prevention, negative electrode film-forming effect, and positive electrode protection can be mentioned, such as cyclohexylbenzene, biphenyl, tert-butylbenzene, carbonate, vinyl ethylene carbonate, difluoroanisole, fluoroethylene carbonate, propane sulfone, succinonitrile, dimethyl vinylene carbonate, etc. In addition, for example, when used for a non-aqueous electrolyte battery known as a lithium polymer battery, the electrolyte can also be used by solidifying the electrolyte for the non-aqueous electrolyte battery with a gelling agent or a cross-linked polymer.
[0178] The lithium secondary battery according to one aspect of the present disclosure has advantages in that, by having the above-described configuration, the battery has a large charge capacity, excellent life characteristics, and can be charged in a short time even at a 1C rate.
[0179] Method for manufacturing negative electrode
[0180] Furthermore, in one embodiment, the present disclosure provides a method of manufacturing a negative electrode according to the present disclosure, comprising:
[0181] applying a negative electrode slurry to at least one side of a negative electrode current collector;
[0182] applying a magnetic field to the applied negative electrode slurry; and
[0183] The negative electrode slurry to which the magnetic field is applied is dried to form a negative electrode active layer.
[0184] The method for manufacturing a negative electrode according to the present disclosure refers to a method for manufacturing the negative electrode of the present disclosure as described above. The method for manufacturing a negative electrode can manufacture a negative electrode having a negative electrode active layer with controlled crystal properties of a negative electrode active material by applying a negative electrode slurry to a negative electrode current collector, applying a magnetic field to the surface of the applied negative electrode slurry, and drying each negative electrode slurry.
[0185] Here, the step of applying the negative electrode slurry is to coat the surface of the moving negative electrode current collector by discharging the negative electrode slurry containing a carbon-based negative electrode active material. This step can be applied by any method conventionally used in the art without particular limitation, but preferably uses a die coating method. The die coating method can be performed using a slot die with a gasket for controlling the discharge conditions of the negative electrode slurry. In this case, by controlling the shape and position of the gasket, the load amount, application thickness, etc. of the negative electrode slurry applied to the negative electrode current collector can be easily controlled.
[0186] At the same time, the step of applying a magnetic field to the negative electrode slurry can control the crystal properties of the negative electrode active material contained in the negative electrode slurry. Specifically, the step can be to apply a magnetic field to the surface of the negative electrode slurry applied to the negative electrode current collector so that the ab axis crystal plane of each carbon-based negative electrode active material contained in the negative electrode slurry is aligned to have a high angle with respect to the negative electrode current collector.
[0187] In this case, the magnetic field can be applied by the magnetic parts provided on the upper and lower parts of the negative electrode current collector, which move with the negative electrode slurry applied to the surface. The polarities of the magnetic parts provided on the upper and lower parts can be different from each other.
[0188] Furthermore, the orientation index (OI) of the carbon-based negative active material contained in each negative electrode slurry can be adjusted by the intensity of the applied magnetic field, the application time, etc., and thus, the step of applying the magnetic field can be performed under a predetermined magnetic field intensity condition.
[0189] Specifically, the step of applying a magnetic field can be applied with a magnetic field in the range of 10,000G (Gauss) or less, specifically, the magnetic field can be applied with an intensity in the following ranges: 1,000G to 7,000G, 2,000G to 6,000G, 1,500G to 5,000G, 1,500G to 4,500G, 4,000G to 7,000G, 2,000G to 4,000G, 2,500G to 3,500G, 3,000G to 6,500G, or 2,700G to 3,300G.
[0190] In addition, the step of applying a magnetic field can be performed for 1 second to 20 seconds, more specifically, for 1 second to 15 seconds, 1 second to 10 seconds, 5 seconds to 20 seconds, 10 seconds to 20 seconds, 11 seconds to 18 seconds, 1 second to 5 seconds, 7 seconds to 13 seconds, or 6 seconds to 11 seconds.
[0191] As an example, in the step of applying the magnetic field, a magnetic field of 3,000±50 G may be applied to the negative electrode slurry for 9 to 11 seconds.
[0192] In addition, as described above, the step of applying a magnetic field can be performed by introducing magnetic portions to the upper and lower portions of the applied negative electrode slurry. However, the size of the magnetic portions can be adjusted to be larger than the size of the negative electrode slurry so that the magnetic field applied to the negative electrode slurry can be uniformly applied to the entire surface of the negative electrode slurry. For example, the length ratio of the magnetic portions based on the length in the width direction of the negative electrode slurry can be in the range of 105% to 200%. Specifically, the length ratio of the magnetic portions based on the length in the width direction of the negative electrode slurry can be in the range of 110% to 180%, 110% to 160%, 110% to 140%, 110% to 130%, 130% to 150%, or 105% to 120%.
[0193] By controlling the magnetic field strength, application time, and / or magnetic portion size as described above in the step of applying the magnetic field, the present disclosure can be uniformly implemented so that the orientation index (OI) of the carbon-based negative active material contained in the negative electrode slurry satisfies a predetermined range.
[0194] In addition, the step of forming the negative electrode active layer may include the steps of drying the negative electrode slurry and rolling the dried negative electrode slurry.
[0195] In this case, the step of drying the negative electrode slurry may be applied in a method capable of maintaining the orientation of the carbon-based negative electrode active material included in the negative electrode active layer without particular limitation.
[0196] For example, the drying step may be performed by applying heat energy to the negative electrode slurry using a hot air dryer, a vacuum oven, or the like to dry the negative electrode slurry.
[0197] In addition, the step of rolling the dried negative electrode slurry increases the density of the negative electrode active layer by applying pressure to the dried negative electrode slurry using a roller press, etc. At this time, the rolling may be performed under a temperature condition higher than room temperature.
[0198] Specifically, rolling may be performed at a temperature ranging from 50°C to 100°C, more specifically, from 60°C to 100°C, 75°C to 100°C, 85°C to 100°C, 50°C to 90°C, 60°C to 80°C, or 65°C to 90°C.
[0199] In addition, rolling can be performed at a rolling speed within the range of 2 m / sec to 7 m / sec, more specifically, rolling can be performed at a rolling speed within the range of 2 m / sec to 6.5 m / sec, 2 m / sec to 6 m / sec, 2 m / sec to 5.5 m / sec, 2 m / sec to 5 m / sec, 2 m / sec to 4.5 m / sec, 2 m / sec to 4 m / sec, 2.5 m / sec to 4 m / sec, 2.5 m / sec to 3.5 m / sec, 3.5 m / sec to 5 m / sec, 5 m / sec to 7 m / sec, 5.5 m / sec to 6.5 m / sec, or 6 m / sec to 7 m / sec.
[0200] In addition, the rolling may be performed under a pressure condition within a range of 50 MPa to 200 MPa, specifically, 50 MPa to 150 MPa, 50 MPa to 100 MPa, 100 MPa to 200 MPa, 150 MPa to 200 MPa, or 80 MPa to 140 MPa.
[0201] By performing roll pressing of the dried negative electrode slurry under the above temperature, speed and / or pressure conditions, the present disclosure can increase the energy density of the negative electrode while minimizing changes in the orientation index of the carbon-based negative active material contained in the formed negative active layer.
[0202] Hereinafter, the present disclosure will be described in more detail through Examples and Experimental Examples.
[0203] However, the following Examples and Experimental Examples merely illustrate the present disclosure, and the present disclosure is not limited to the following Examples and Experimental Examples.
[0204] Examples 1 to 4 and Comparative Examples 1 to 3. Manufacturing of Negative Electrodes for Lithium Secondary Batteries
[0205] As a carbon-based negative electrode active material, primary particles in the form of flakes are assembled to form secondary particles of artificial graphite (average particle diameter (D 50 ):16±0.1μm) and prepare silicon dioxide (SiO2, average particle diameter (D 50): 8.0±0.1 μm). In addition, styrene-butadiene rubber (SBR) as a binder and carboxymethyl cellulose (CMC) as a thickener were prepared.
[0206] Then, 96 parts by weight of the first artificial graphite, 1.5 parts by weight of carboxymethyl cellulose (CMC), and 2.5 parts by weight of styrene-butadiene rubber (SBR) were mixed with water to a solid content of 50% to prepare a first negative electrode slurry.
[0207] In addition, a second negative electrode slurry was prepared by mixing 96 parts by weight of the second artificial graphite and silicon dioxide (SiO2), 1.5 parts by weight of carboxymethyl cellulose (CMC), and 2.5 parts by weight of styrene-butadiene rubber (SBR) with water so that the solid content became 50%. At this time, the content ratio of the second artificial graphite and silicon dioxide (SiO2) in the second negative electrode slurry constituting the second negative electrode active layer was adjusted based on the total negative electrode active material contained in the second negative electrode slurry, as shown in Table 1 below.
[0208] After preparing each negative electrode slurry, a dual-die coater was used to simultaneously cast the first and second negative electrode slurries onto a copper sheet (thickness: 10 μm) that was being rolled to a roll (transfer speed: 5 m / min). The loading amounts of the first and second negative electrode slurries were adjusted to be the same.
[0209] A permanent magnet having a length ratio of 110% to 120% of the length in the width direction of the applied negative electrode slurry is set on the upper part of the negative electrode slurry and the lower part of the negative electrode current collector, and a magnetic field is applied with a magnetic field strength of 3,000±20G. At this time, the time for applying the magnetic field is shown in Table 1. The negative electrode slurry to which the magnetic field is applied is hot air dried to form a negative electrode in the form of a first negative electrode active layer and a second negative electrode active layer sequentially stacked on the negative electrode current collector. The formed negative electrode active layer is rolled at 50±1°C under a pressure of 100MPa to 150MPa and a conveying speed of 3m / second to prepare a negative electrode for a lithium secondary battery (each average thickness of the negative active polarity layer: 120±5μm, load: 21mg / cm 2 Up to 30mg / cm 2 ).
[0210] For each manufactured negative electrode, X-ray diffraction (XRD) spectra of the first negative electrode active layer and the second negative electrode active layer were measured. At this time, for the first negative electrode active layer, after measuring the X-ray diffraction (XRD) spectrum of the second negative electrode active layer, the second negative electrode active layer was peeled off and removed, and then the exposed surface of the first negative electrode active layer was subjected to X-ray diffraction measurement. In addition, the measurement conditions of X-ray diffraction (XRD) are as follows:
[0211] -Target: Cu (Kα ray) graphite monochromator.
[0212] - Slits: Divergence slit = 1 degree, Receiving slit = 0.1 mm, Scattering slit = 1 degree
[0213] -Measurement area: (110) plane: 76.5°<2θ<78.5° / (004) plane: 53.5°<2θ<56.0°.
[0214] From the spectra measured under the above conditions, the average orientation index (OI) of the carbon-based negative electrode active material contained in each negative electrode active layer was calculated using Formula 1. The results are shown in Table 1:
[0215] [Formula 1]
[0216] OI=I 004 / I 110
[0217] In formula 1,
[0218] I 004 represents the area of the peak representing the (004) crystal plane of the carbon-based negative electrode active material in the X-ray diffraction spectrum (XRD) analysis of the negative electrode active layer,
[0219] I 110 It represents the area of the peak representing the (110) crystal plane of the carbon-based negative electrode active material in the X-ray diffraction spectrum (XRD) analysis of the negative electrode active layer.
[0220] [Table 1]
[0221]
[0222]
[0223] Comparative Example 4. Manufacturing a negative electrode for a lithium secondary battery
[0224] The first negative electrode slurry and the second negative electrode slurry were prepared using the same method as in Example 1, and the prepared first negative electrode slurry and the second negative electrode slurry were simultaneously cast on a copper sheet (thickness: 10 μm) using a dual-die coating machine. At this time, the cast first negative electrode slurry and the second negative electrode slurry had the same loading amount, and the total loading amount of the first negative electrode slurry and the second negative electrode slurry was 21 mg / cm 2 Up to 30mg / cm 2 .
[0225] A permanent magnet with a length ratio of 110% to 120% of the width of the applied negative electrode slurry was placed above the negative electrode slurry and below the negative electrode current collector. A magnetic field of 10,000 ± 100 G was applied to the surface of the negative electrode slurry for 15 seconds. The negative electrode slurry, with the magnetic field applied, was hot-air dried to form a negative electrode in the form of a first negative electrode active layer and a second negative electrode active layer sequentially stacked on the negative electrode current collector. The formed negative electrode active layer was roll-pressed at 50 ± 1°C under a pressure of 100 MPa to 150 MPa and a conveying speed of 3 m / s to produce a negative electrode for a lithium secondary battery.
[0226] For the negative electrode manufactured by the same method as in Example 1, the first negative electrode active layer and the second negative electrode active layer were subjected to X-ray diffraction spectroscopy (XRD) to measure the spectrum. From the measured spectrum, the average orientation index (OI) of each negative electrode active layer was calculated using Formula 1. The orientation indexes (OI) of the first negative electrode active layer and the second negative electrode active layer were 4 and 24, respectively, and their ratio (OI 第一 / OI 第二 ) is 0.17.
[0227] Examples 5 to 8 and Comparative Examples 5 to 8. Manufacturing of Lithium Secondary Batteries
[0228] LiNi with a particle size of 5 μm was prepared as the positive electrode active material. 0.7 Co 0.1 Mn 0.1 Al 0.1 O 2 , a carbon-based conductor, and polyvinylidene fluoride as a binder were mixed in a weight ratio of 94:3:3 and mixed in N-methylpyrrolidone (NMP) to become a solid content of 50% to prepare a positive electrode slurry.
[0229] The positive electrode was fabricated by casting the prepared positive electrode slurry on an aluminum sheet, drying it in a vacuum oven at 120°C, and then roll-pressing it.
[0230] Separators containing 18 μm polypropylene were interposed between the positive electrodes obtained above and the negative electrodes manufactured in Examples 1 to 4 and Comparative Examples 1 to 4, respectively, and inserted into a case, followed by injection of an electrolyte composition to assemble a 1 Ah-class lithium secondary battery.
[0231] At this time, the type of negative electrode applied to each lithium secondary battery is shown in Table 2 below.
[0232] [Table 2]
[0233] Type of negative electrode used Example 5 The negative electrode manufactured in Example 1 Example 6 The negative electrode manufactured in Example 2 Example 7 The negative electrode manufactured in Example 3 Example 8 The negative electrode manufactured in Example 4 Comparative Example 5 The negative electrode manufactured in Comparative Example 1 Comparative Example 6 The negative electrode manufactured in Comparative Example 2 Comparative Example 7 The negative electrode manufactured in Comparative Example 3 Comparative Example 8 The negative electrode prepared in Comparative Example 4
[0234] Experimental example.
[0235] In order to evaluate the performance of the negative electrode according to an embodiment of the present disclosure, the following experiments were performed on each of the negative electrodes and lithium secondary batteries manufactured in Examples and Comparative Examples.
[0236] 1) Lifespan characteristics evaluation
[0237] Each of the lithium secondary batteries manufactured in Examples 5 to 8 and Comparative Examples 5 to 8 was activated by charging to 4.35 V at a rate of 0.3 C under CC-CV conditions at a temperature of 25° C. and discharging to 3.0 V at a rate of 0.3 C under CC conditions.
[0238] Each activated lithium secondary battery was charged to 4.35V under CC-CV conditions at a rate of 1.0C at a temperature of 25°C, and discharged to 3.0V under CC conditions at a rate of 1.0C as 1 cycle, and 1 charge and discharge cycle of each lithium secondary battery manufactured in the embodiment and the comparative example was performed. At this time, the capacity during charging and discharging was measured to determine the charge and discharge capacity of the first cycle. Then, 499 charge and discharge cycles of each lithium secondary battery were performed, totaling 500 charge and discharge cycles. In this case, the charge and discharge capacity of the 500th cycle was determined at the end of the last cycle. Based on the measured charge and discharge capacity of the first cycle, the charge and discharge capacity retention rate of the 500th cycle was calculated. The results are shown in Table 3 below.
[0239] 2) 1C rate fast charging evaluation
[0240] Each of the lithium secondary batteries manufactured in Examples 5 to 8 and Comparative Examples 5 to 8 was activated by charging to 4.35 V at a rate of 0.3 C under CC-CV conditions at 25° C. and discharging to 3.0 V at a rate of 0.3 C under CC conditions.
[0241] Each activated lithium secondary battery was charged at 25°C using a constant current-constant voltage (CC-CV) method, and the time required for the state of charge (SOC) to reach 80% was measured. Charging was performed as follows: constant current (CC) charging was performed at a current rate of 1.0C until the voltage reached 4.35V, followed by constant voltage (CV) charging to maintain 4.35V, and the charge was cut off when the current reached a rate of 0.005C. The measured charging times are shown in Table 3 below.
[0242] [Table 3]
[0243]
[0244] As shown in Table 3 above, it can be seen that the negative electrode for a lithium secondary battery according to one aspect of the present disclosure not only has excellent lifespan characteristics but also completes charging at a fast speed under a 1C rate condition.
[0245] Specifically, the negative electrode of the embodiment exhibited a high charge and discharge capacity retention rate of 80% or more after 500 charge and discharge cycles. In addition, the secondary battery of the embodiment including such a negative electrode reached a state of charge (SOC) of 80% in a short time of less than 25 seconds under standard constant current-constant voltage (CC-CV) charging conditions at a 1C rate.
[0246] On the other hand, the negative electrode of Comparative Example 3, which does not contain silicon-based negative electrode active material silicon dioxide (SiO2) as the negative electrode active material, exhibited a relatively high charge and discharge capacity retention rate of about 95% after 500 charge and discharge cycles; but compared with the negative electrode of the embodiment containing silicon dioxide (SiO2), the charge and discharge capacity of one cycle was found to be significantly lower.
[0247] In addition, it was found that the negative electrode of other comparative examples containing silicon dioxide (SiO2) had a large capacity during charge and discharge. However, it was found that the time for the negative electrode to reach 80% state of charge (SOC) under standard constant current-constant voltage (CC-CV) charging conditions at a 1C rate was 39 seconds or longer.
[0248] This indicates that by controlling the orientation index (OI) of the carbon-based negative electrode active material and the position and content of the silicon-based negative electrode active material contained in each negative electrode active layer, it is possible to simultaneously improve i) the life characteristics of the negative electrode and ii) the charging speed under standard charge rate conditions.
[0249] From these results, it can be seen that the negative electrode for a lithium secondary battery according to one aspect of the present disclosure has large charge and discharge capacity and excellent life characteristics, and a lithium secondary battery including the same can be charged in a short time even at a 1C rate.
[0250] As above, the present disclosure is described in more detail through the embodiments. However, since the configuration described in the drawings or embodiments described herein is only one embodiment of the present disclosure and does not represent all the technical spirit of the present disclosure, it should be understood that when submitting this application, the present disclosure covers various equivalent solutions, modifications and alternatives.
[0251] Therefore, the technical scope of the present disclosure is not limited to what is described in the detailed description of the specification, but should be determined by the claims of this patent.
Claims
1. A negative electrode, comprising a negative electrode current collector, a first negative electrode active layer disposed on at least one side of the negative electrode current collector and containing a first carbon-based negative electrode active material, and a second negative electrode active layer disposed on the first negative electrode active layer and containing a second carbon-based negative electrode active material and a silicon-based negative electrode active material; wherein the first negative active layer has an orientation index (OI) in the range of 5 to 15 according to the following formula 1 第一 ),and satisfying the following formula 2 within the range of 0.2 to 0.6: [Formula 1] OI=I 004 / I 110 [Formula 2] OI 第一 / OI 第二 In Formula 1 and Formula 2, I 004 represents the area of the peak representing the (004) crystal plane of the carbon-based negative electrode active material in the X-ray diffraction spectrum (XRD) analysis of the negative electrode active layer, I 110 represents the area of the peak representing the (110) crystal plane of the carbon-based negative electrode active material in the X-ray diffraction spectrum (XRD) analysis of the negative electrode active layer, OI 第一 represents an orientation index of the first carbon-based negative electrode active material contained in the first negative electrode active layer, OI 第二 It represents the orientation index of the second carbon-based negative electrode active material contained in the second negative electrode active layer.
2. The negative electrode according to claim 1, wherein based on the weight of the second negative electrode active layer, 1 wt% to 25 wt% of the silicon-based negative electrode active material is contained.
3. The negative electrode according to claim 1, wherein the orientation index (O.I) of the first negative electrode active layer is within the range of 7 to 12.
4. The negative electrode according to claim 1, wherein the first carbon-based negative electrode active material and the second carbon-based negative electrode active material each contain one or more types of natural graphite and artificial graphite, respectively.
5. The negative electrode according to claim 1, wherein the silicon-based negative electrode active material comprises one or more types of silicon (Si), silicon carbide (SiC), and silicon oxide (SiO q , where 0.8≤q≤2.5).
6. The negative electrode according to claim 1, wherein the total thickness of the first negative electrode active layer and the second negative electrode active layer is within the range of 50 μm to 500 μm.
7. A method of manufacturing the negative electrode according to claim 1, comprising: applying a negative electrode slurry to at least one side of a negative electrode current collector; applying a magnetic field to the applied negative electrode slurry; and drying the negative electrode slurry to which the magnetic field has been applied to form a negative electrode active layer.
8. The method of manufacturing a negative electrode according to claim July, wherein the step of applying the magnetic field is carried out for a duration of 1 second to 20 seconds.
9. The method of manufacturing a negative electrode according to claim 7, wherein the step of applying the magnetic field is carried out at a magnetic field strength within the range of 1,000 G to 7,000 G.
10. A lithium secondary battery, comprising: an electrode assembly including a positive electrode, the negative electrode according to claim 1, and a separator disposed between the positive electrode and the negative electrode; and an electrolyte composition impregnating the electrode assembly.
11. The lithium secondary battery according to claim 10, wherein the positive electrode includes a positive electrode active layer disposed on at least one side of a positive electrode current collector and containing one or more types of lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2: [Chemical Formula 1] Li x [Ni y Co z Mr w M 1 v ]O2 [Chemical Formula 2] LiM 2 p Mn 1-p O4 In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more types of elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, x, y, z, w, and v are respectively 1.0 ≤ x ≤ 1.30, 0.5 ≤ y < 1, 0 < z ≤ 0.3, 0 < w ≤ 0.3, and 0 ≤ v ≤ 0.1, and y + z + w + v = 1, M 2 Ni, Co or Fe, p is 0.05 ≤ p ≤ 1.
0.
12. The lithium secondary battery according to claim 11, wherein the positive electrode active material comprises one or more types of: LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2、LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2、LiNi 0.7 Mn 1.3 O4、LiNi 0.5 Mn 1.5 O4 and LiNi 0.3 Mn 1.7 O4.
13. The lithium secondary battery according to claim 10, wherein the electrode assembly is a stacked electrode assembly, a Z-shaped electrode assembly, or a Z-shaped stacked electrode assembly.
Citation Information
Patent Citations
Grip Tok Detachable Smartphone Case
KR1020230105352A